Xosé Carlos Arias y Antón Costas. La torre de la arrogancia. Políticas y mercados después de la crisis. - Gutiérrez, Ricardo (Estudios económicos, 2013)
Xosé Carlos Arias y Antón Costas. La torre de la arrogancia. Políticas y mercados después de la crisis.